2018
DOI: 10.1002/jca.21626
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation, bleeding, and clotting at donor plasmapheresis

Abstract: This article is based on a question of a colleague from North America how coagulation could be triggered between a donor's arm and a fistula needle during plasma donation (synonymous with donor plasmapheresis). The technique of venipuncture and citrate anticoagulation are described. Uncommon and rare problems such as prolonged bleeding, scarring, and thrombosis in plasma donors are discussed. If venous puncture and citrate: blood flow ratio at 1:16 are correctly performed, however, there will be no anticoagula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 8 publications
3
5
0
Order By: Relevance
“…Beeck et al have already shown in a prospective study that a TSC:blood flow ratio of 1:16 gives the best results for the production of coagulation factors V, VIII, and IX without activation of hemostasis 33 . This is consistent with our experience that if the venipuncture was performed correctly and the TSC:blood flow ratio at 1:16 was correct, no anticoagulation or bleeding problems would occur 14 …”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Beeck et al have already shown in a prospective study that a TSC:blood flow ratio of 1:16 gives the best results for the production of coagulation factors V, VIII, and IX without activation of hemostasis 33 . This is consistent with our experience that if the venipuncture was performed correctly and the TSC:blood flow ratio at 1:16 was correct, no anticoagulation or bleeding problems would occur 14 …”
Section: Discussionsupporting
confidence: 91%
“…This resulted in an average CIR between 0.33 and 0.37 mg/kg/min. It follows that the calculated CIR is in agreement with the earlier reports, 10,29 and that an individualized dosing of TSC in plasma donations with a low flow ratio of TSC 1:16 to blood is not required 14 …”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations